Perceived discrimination in the discourse of second-wave Latin American immigrants in Brisbane. Issue 1 (1st March 2020) - Rojas-Lizana, Sol
Perceived discrimination (PD) in the field of discourse analysis is the study of discourse that focuses on the perspectives of the victims of discrimination, exploring what they say and how they say it. This article studies the discourse of PD of ten Latin American immigrants to Brisbane, during semi-structured, co-constructed interviews. Data were classified into a typology of discrimination that identified verbal and non-verbal forms. The analysis of these forms shows that the verbal form 'microagressions' dominated the discourse and that most experiences had a connection with 'accent' as a triggering factor. In some cases, participants were 'new' to discrimination and they reported confusion regarding the nature of the experience and a deep emotional weight. Other participants reported discrimination as pervasive and covert, mainly occurring in the workplace. Participants resorted to several discursive strategies when conveying their experiences: mitigation strategies when wanting to minimize it and hedging and repetition to convey urgency and pervasiveness. Metaphorical expressions relating to illness and injury were also used to express the powerful effect of discrimination on people.